The Effect of Spatial Configuration on the Movement Distribution Behavior: The Case Study of Constantine Old Town (Algeria) - Fareh, F.; Alkama, D. (Engineering, Technology & Applied Science Research, 2022)
This study examines the correlation between spatial configuration and movement behavior within the traditional urban fabric of Constantine city. The distribution of pedestrian movement was modeled in relation to the syntactic measures of street networks. The results showed a significant correlation between pedestrian volume with integration and choice measures at the global scale (Rn), however, the local scale (R3) did not capture the variance and the presence of the movement. The measures of connectivity that are used to describe the density of street connections also revealed a weak association with the presence of people within the dense traditional layout of the research area. The results support the previous findings of space syntax theory, asserting the important role of the street network structure in assessing the configurational accessibility of a given spatial layout. However, we do not assert its exclusive role in determining the natural-movement patterns. Therefore, consideration should be given to more external indicators, like the interaction with land use and socioeconomic activities. We conclude that examining the network radius-based attributes of street configuration can provide a clear understanding of spatial variations in pedestrian activity within multi-scale walkable areas, which helps planners improve the livability of the city by designing more friendly walkable streets.